Foreign experience of transition to a “green” economy and possibilities of its application in the regions of Uzbekistan - Aminov Fazlitdin Bakhadirovich (THE INNOVATION ECONOMY, 2026)
The article analyzes strategies for transition to a “green” economy using developed and developing countries as examples. In addition, the southern regions of Uzbekistan were used as an example to assess the possibilities of applying this experience in local conditions. Based on global are proposed experience, effective approaches and principles for Uzbekistan.